Finding Comfort in the Discomfort of Being Multiracial: Lessons from my Schooling. (3rd April 2017) - Ginsberg, Ricki
Abstract: The multiracial population increased by 32% between 2000 and 2010 and represents 9 million people in the United States. The author reflects on her lived experiences of being multiracial but with visibly White skin. She details the lessons she learned about her multiracial identity—from her early positioning as a young student to her role as a teacher of other multiracial students. The article presents the complexities experienced by students with multiracial identities and how their self-conceptions of identity may be complicated when they visually appear to be White.